The Law Impact on Murder Trial From Balinese Customary Law Perspective (Case Study In Desa Pakraman Sukawati) - Anak Agung Mas Adi Trinaya Dewi; Ni Made Trisna Dewi (Sociological Jurisprudence Journal, 2020)
This study aims to analyze what legal sanction and what consequences for the heirs trying to commit the murder of the inheritors in the perspective of Balinese customary law. The research method used is empirical research that is the observational and field study research in the Desa Pakraman Sukawati. Data were collected through observation. The result of the research is that the legal sanction for the heirs in perspective of Balinese customary law is a sentence of sanction given by Balinese traditional court law. The criminal matters are resolved in traditional court and it is not yet exist in the criminal code or state law. This sanction for violation of mistreatment of the heir tried to murder the inheritors occurred in Desa Pakraman Sukawati is determined by village peace judge. This is specially done by Prajuru Adat (Balinese indigenous custom village officers). The legal consequences described on Balinese customary law are based on Article 838 of the Civil Code. It states that it is one of those who has been convicted or blamed for killing or attempting to kill the inheritors, the consequence is that the inheritance is void although the heirs are entitled for inheritance. It is a principle that every person including a person who has inheritance rights of inheritance does not receive anything. This has been determined by law and it is excluded from inheritance due to inappropriateness (onwaardig) to receive inheritance.